2018
DOI: 10.1177/0197918318767928
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the “Liberal Paradox” from the Inside: Evidence from the Swedish Migration Courts

Abstract: Courts are influential actors during the implementation of immigration policies in liberal democracies. The “liberal paradox” thesis stipulates that courts are driven by logics that hamper restrictionist immigration policies. This study contributes to this theory by exploring the norm construction of impartiality among judicial workers in Swedish migration courts when deciding asylum appeals. Its findings contradict the liberal paradox assumption that courts act according to inner logics that benefit immigrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…3 See Martén (2015), Hjalmarsson (2019), andJohannesson (2018) for studies of political bias in Swedish judicial decision-making. become a lay judge by contacting one of the political parties, which control the selection process.…”
Section: Case and Methodologymentioning
confidence: 99%
“…3 See Martén (2015), Hjalmarsson (2019), andJohannesson (2018) for studies of political bias in Swedish judicial decision-making. become a lay judge by contacting one of the political parties, which control the selection process.…”
Section: Case and Methodologymentioning
confidence: 99%
“…Where the sovereign imperative to exert territorial control coincides with a state’s expressive commitment to human rights, a liberal paradox has been argued to result: immigration is viewed skeptically and heavily restricted, and yet states admit at least some unwanted immigrants and can often accommodate their human rights demands (Joppke 1998b). It is much debated which mechanisms effect this outcome, with some arguing that logics of globalization are primarily responsible for constraining states’ capacities to exclude as they wish and others insisting that state-internal rule of law prerogatives most stifle sovereign logics of exclusion (Hollifield, Hunt, and Tichenor 2008; Johannesson 2018; Joppke 1998b). However, although this debate shows that various mechanisms have often kept sovereign states sufficiently in check to thwart at least some of their impulses to exclude and ignore outsiders’ claims, a deeper question about the positioning and sturdiness of these claims within systems of sovereign governance has not so far been addressed.…”
Section: Sovereign Disrespectmentioning
confidence: 99%
“…Reliance on such ideologies can result in inconsistent and unfair outcomes, especially for those who do not have access to legal assistance. Critical discourse analysis of the AAT's credibility assessment guidelines and a set of anonymized published decisions has found that credibility assessments rely on flawed language ideologies (Smith-Khan, 2017a, 2017b, 2018. In asylum decision-making, such beliefs about language are similar to and in some cases overlap with lay assumptions about psychology and human behaviour, which existing studies have identified as equally problematic for credibility assessments (see, e.g.…”
Section: Credibility Assessments In Australian Refugee Visa Decision-makingmentioning
confidence: 99%
“…Furthermore, decision-makers work in institutional settings, and as such are influenced in how they do their work by the culture of such settings, their employment conditions, institutional guidelines and most probably also by broader political discourses. This means that the politics of the governing party, especially of those responsible for the Immigration Department itself, can result in what has been termed a culture of disbelief or suspicion (Bohmer & Shuman, 2018;Jubany, 2011;Piller et al, 2021) or one in which scepticism is viewed as impartiality (Johannesson, 2018). Such an environment is likely to affect civil servants working within this part of government, including Immigration Department and IAA decision-makers.…”
Section: Combatting Problematic Language Ideologies In Court: Challenges and Opportunitiesmentioning
confidence: 99%